Socorro Chatbot: Promoting regular blood donation through a conversation agent - Serrano, Paulo Henrique Souto Maior (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
The conversation agent Socorro is a project that aims to promote voluntary and regular blood donation through the exchange of text messages between the donor and the chatbot. The solution was developed using the Dialogflow platform complemented by a webhook in NodeJS and integrated with the Telegram instant messaging platform. In Brazil, blood donation is a voluntary practice that requires motivation, availability and interest on the part of the donor. Socorro seeks to promote regular donation, allowing donors to access their donation history, receive reminders about the availability of donating again, form donation groups with friends. It also creates a communication channel between the blood center and the user to invite specific blood types seeking to enhance the donor experience. In the case study presented in this research, we also sought to demonstrate the implementation of specific usability heuristics for chatbots in interactions carried out by Socorro. Conversation robots have significant potential to accomplish tasks normally performed by graphical interfaces, the implementation of this type of solution can bring benefits to users in terms of familiarity, practicality and routine, since it uses instant messengers, solutions that are already in common use.